The Popular Education: Interview with Óscar Jara Holliday - Jara Holliday, Óscar (2019)
In this interview, the prominent Peruvian-Costa Rican popular educator and sociologist, Dr. Óscar Jara Holliday, explains the origins and particularities of popular education. In his own words, popular education “should have a transformative political notion, that is, an education that should allow society to have a social, democratic, fair, equitable structure and, therefore, the main subjects of the educational processes must be those that drive these political-pedagogical processes. From that political-pedagogical vision of a popular society project, we can talk about a popular education”.